Land Rehabilitation on Post-fire Area with Different Types of Soil in Gunung Mas Regency, Central Kalimantan - Arin Annisa Fathia; Iwan Hilwan; Cahyo Wibowo (Media Konservasi, 2019)
Forest and land fires can cause damage to forest ecosystems. Repeated fires cause the natural succession to be disrupted. Therefore, based on these problems, to improve the productivity of land after fires in Central Kalimantan, rehabilitation efforts needs to be done. This study aims to analyze the growth response of forestry plants in post-fire area with different soil types. This study consisted of six combinations of treatments namely controls (B0C1 and B0C2), treatment of dolomite, biochar, and compost (B1C1 and B1C2), and treatment of dolomite and NPK (B2C1 and B2C2) that planted randomized and rows Trees species were used in this research were Paraserianthes falcataria, Anthocephalus cadamba, Acacia mangium, and Campnosperma auriculata. Soil samples were also collected for analysis of soil physical and chemical properties on laboratory. This study showed that fertilization treatment significantly affected the increase of height and diameter of four trees species, while planting techniques (randomized and rows) did not significantly affected the increase of height and diameter of four trees species. Dolomite, biochar, and compost application significantly affected the increase of height and diameter of four trees species that planted randomized and rows (B1C1 and B1C2) in Podsol soil. Besides that, NPK and dolomite application significantly affected the increase of height and diameter of four trees species planted by randomized and rows (B2C1 and B2C2) in Acrisol soil. The fastest growth rate was A. mangium followed by P. falcataria, A. cadamba, and C. auriculata on Podsol and Acrisol soil. Based on the observations, P. falcataria, A. cadamba, A. mangium, and C. auriculata are recommended to be planted on both types of soil. Keywords: forestry plants, growth respon, Gunung Mas Regency, land rehabilitation, soil types